Interactive Letter and Number Learning Machines For Early Childhood - Mochamad Fajar Wicaksono; Myrna Dwi Rahmatya; Angga Rinaldi (CCIT Journal, 2020)
The purpose of this study is to design and create interactive learning machines for letters and numbers for early childhood. The machine designed is an interactive learning machine so that early childhood is interested in learning and can learn independently. Arduino Mega2560 is used as the main processor on this machine. On this machine, there are three modes, namely learning mode, question mode, and counting mode. In learning mode, Arduino will read every button input pressed, display on the LCD and make a sound through DF Player in accordance with the input received. In the question mode, Arduino will issue a question in the form of sound and wait for an answer via the input button found on the device. In arithmetic mode, Arduino will read the input of 10 LDR sensors covered by ice-cream sticks placed by young children and make sounds related to the amount. Questions on tools can be changed by using an android application designed in this study. Based on the test results, this tool has been running well where all modes can be run 100% whether it is learning mode, question mode, and counting mode. Keyword— Arduino, Early childhood, LCD, DF Player, Letters, and Numbers, Counting